Odpowiedź :
Odpowiedź:
a) 7x-3+4x-2x+5+3x = 12x + 2
b)3,1a +0,8a -a -0,8 = 2,9a - 0,8
c) 2/7 y +4+2y -5 +5/7 y = 3y - 1
2.Oblicz wartość wyrażenia dla podanej wartości zmiennej:
3n-6n+3-4+5n -1+0,2
dla n=1,4
3*1,4 - 6*1,4 + 3 - 4 + 5*1,4 - 1 + 0,2 =
= 4,2 - 8,4 + 3 - 4 + 7 - 1 + 0,2 = 1
Odpowiedź:
1.
a)
7x - 3 + 4x - 2x + 5 + 3x = 12x - 8
b)
3,1a + 0,8a - a - 0,8 = 2,9a - 0,8
c)
2/7y + 4 + 2y - 5 + 5/7y = 7/7y + 2y - 1 = 3y - 1
2.
3n - 6n + 3 - 4 + 5n - 1 + 0,2 = 2n - 1,8 = 2 * 1,4 - 1,8 = 2,8 - 1,8 = 1